Chimpanzees (Pan troglodytes) can wait, when they choose to: a study with the hybrid delay task - Beran, Michael J.; Evans, Theodore A.; Paglieri, Fabio; McIntyre, Joseph M.; Addessi, Elsa; Hopkins, William D. (Animal cognition, 2014)
Self-control has been studied in nonhuman animals using a variety of tasks. The inter-temporal choice (ITC) task presents choices between smaller–sooner (SS) and larger–later (LL) options. Using food amounts as rewards, this presents two problems: (a) choices of the LL option could either reflect self-control or instead result from animals’ difficulty with pointing to smaller amounts of food; (b) there is no way to verify whether the subjects would not revert their choice for the LL option, if given the opportunity to do so during the ensuing delay. To address these problems, we have recently introduced a new protocol, the hybrid delay task, which combines an initial ITC with a subsequent accumulation phase in which selection of the SS option leads to its immediate delivery, but choice of the LL option then leads to one-by-one presentation of those items that continues only as long as the subject does not eat any of the accumulated items. The choice of the LL option therefore only reflects self-control when the number of items obtained from LL choices during the accumulation phase is higher than what could be received in the SS option. Previous research with capuchin monkeys demonstrated that their apparent self-control responses in the ITC task may have overestimated their general self-control abilities, given their poor performance in the hybrid delay task. Here, chimpanzees instead demonstrated that their choices for the LL option in the ITC phase of the hybrid delay task were confirmed by their ability to sustain long delays during accumulation of LL rewards.